Perspective: Time-Restricted Eating Compared with Caloric Restriction: Potential Facilitators and Barriers of Long-Term Weight Loss Maintenance. Issue 2 (19th January 2021) - O'Connor, Sydney G; Boyd, Patrick; Bailey, Caitlin P; Shams-White, Marissa M; Agurs-Collins, Tanya; Hall, Kara; Reedy, Jill; Sauter, Edward R; Czajkowski, Susan M
ABSTRACT: A growing body of literature examines the potential benefits of a time-based diet strategy referred to as time-restricted eating (TRE). TRE, a type of intermittent fasting, restricts the time of eating to a window of 4–12 h/d but allows ad libitum intake during eating windows. Although TRE diets do not overtly attempt to reduce energy intake, preliminary evidence from small studies suggests that TRE can lead to concomitant reduction in total energy, improvements in metabolic health, and weight loss. Unique features of the TRE diet strategy may facilitate adherence and long-term weight loss maintenance. In this Perspective, we explore the potential multilevel (i.e., biological, behavioral, psychosocial, environmental) facilitators and barriers of TRE for long-term weight loss maintenance in comparison with the more commonly used diet strategy, caloric restriction (CR). Compared with CR, TRE may facilitate weight loss maintenance by counteracting physiological adaptations to weight loss (biological), allowing for usual dietary preferences to be maintained (behavioral), preserving executive functioning (psychosocial), and enabling individuals to withstand situational pressures to overeat (environmental). However, TRE may also pose unique barriers to weight loss maintenance, particularly for individuals with poor baseline diet quality, internal or social pressures to eat outside selected windows (e.g., grazers), and competing demands that interfere with the scheduling of eating. Future studies of TRE in free-living individuals should consider the multiple levels of influence impacting long-term adherence and weight loss maintenance. Ultimately, TRE could be one strategy in a toolkit of tailored diet strategies to support metabolic health and weight loss maintenance.